18.6k views
2 votes
How do you expand (x-4)^2 ?

User Jeff Moden
by
5.1k points

2 Answers

4 votes

Answer:

(x - 4)^2 = x^2 - 8*x + 16

Explanation:

(a - b)^2 = a^2 - 2*a*b + b^2

(x - 4)^2 = x^2 - 2*x*4 + 4^2 = x^2 - 8*x + 16

User Omi Harjani
by
4.8k points
5 votes

Answer: x^2 - 8x + 16

Let y = x-4

(x-4)^2 = (x-4)*(x-4)

(x-4)^2 = y*(x-4) ... replace one copy of (x-4) with y

(x-4)^2 = x*y - 4*y .... distribute

(x-4)^2 = x*( y ) - 4( y )

(x-4)^2 = x(x - 4) - 4(x - 4) ... replace y with x-4

(x-4)^2 = x^2-4x-4x+16 .... distribute

(x-4)^2 = x^2 - 8x + 16

User Jay Supeda
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.